Antibiotic Resistance Profiles and Molecular Mechanisms of Campylobacter From Chicken and Pig in China - Tang, Mengjun; Zhou, Qian; Zhang, Xiaoyan; Zhou, Sheng; Zhang, Jing; Tang, Xiujun; Lu, Junxian; Gao, Yushi (Frontiers in Microbiology, 2020)
The purpose of this research was to characterize the antibiotic resistance profiles of Campylobacter spp. derived from chicken and pig feces collected from farms in Jiangsu Province, China, and to analyze the relevant resistance mechanisms among antimicrobial-resistant Campylobacter spp. isolates. Antibiotic susceptibility to nine antibiotic agents was tested with the microdilution method in 93 Campylobacter spp. (45 C. jejuni and 25 C. coli from chickens; 23 C. coli from pigs). High rates of resistance were observed to nalidixic acid (79.6%), erythromycin (75.3%), tetracycline (68.8%), azithromycin (66.7%), ciprofloxacin (64.5%), and gentamicin (35.5%), with a lower resistance rate to florfenicol (8.6%). The prevalence of the tested antibiotic resistance in C. coli was higher than in C. jejuni from chickens. The rate of antimicrobial resistance to ciprofloxacin in C. coli isolates from chickens was 100.0%, and the C. coli isolates from pigs were all resistant to erythromycin (100%). Most of C. jejuni (64.4%) and C. coli (64.5%) isolates displayed multi-drug resistance. All the Campylobacter spp. isolates resistant to fluoroquinolones had the C257T mutation in the gyrA gene. All 64 tetracycline-resistant Campylobacter spp. isolates were positive for the tetO gene. The tetA gene was also amplified in 6.5% of Campylobacter spp. isolates, whereas tetB was not detected among the isolates. The A2075G point mutation in the 23S rRNA gene occurred in 86.1% (62/72) of the macrolides-resistant Campylobacter spp. isolates, and the ermB gene was identified in 49 Campylobacter spp. isolates (30 C. jejuni and 19 C. coli). Amino acid insertions or mutations in the L4 and L22 ribosomal proteins were not linked to macrolide resistance. These results highlight the high prevalence of resistance to multiple antibiotics, particular macrolides, among Campylobacter spp. from chickens and pigs in Jiangsu Province, China, which is probably attributable to the overuse of antimicrobials in chicken and pig production. These findings recommend the more cautious use of critical antimicrobial agents in swine and poultry production. Stringent and continuous surveillance is required to reduce the drug-resistant campylobacteriosis in food animals and humans.